An Embedding Technique for Language-Independent Lecturer-Oriented Program Visualization - Sulistiani, Lisan; Karnalim, Oscar (EMITTER International Journal of Engineering Technology, 2018)
Nowadays, programming is a promising skill to be learned; the demand of programmer is increased. To align with such trend, several Program Visualization (PV) tools have been developed. Using such tool, user can learn how a particular program works through interactive and descriptive visualization. However, most of the tools are language-dependent: they use either language-dependent debugger or code to generate visualization. Such dependency may become a problem when a program written in new programming language is incorporated. Therefore, this paper proposes an embedding technique to handle given issue. To incorporate new programming language, it only needs five language-dependent features to be set. In general, our proposed technique works in threefold: embedding some statements to target program, generating visualization states by running the program with console commands, and visualizing given program based on generated visualization states. According to our evaluation, proposed technique is able to incorporate program written in any programming languages as long as those languages provide required language-dependent features. Further, it is practical to be used since it still have the benefits of conventional PV even though it is designed as a language-independent PV.